Pertimbangan Hukum Hak Asuh Anak di Bawah Umur bagi Ayah Pecandu Narkotika: Analisis Putusan No. 1039/Pdt.G/2023/PA.Lpk Jo No. 89/Pdt.G/2023/PTA.Mdn Jo No. 103K/Ag/2024 - Rizki Ardilia, Novi; Purba, Hasim; Sembiring, Rosnidar (JOM, 2025)
This study aims to analyze the judges’ legal considerations in granting child custody to a father who is a drug addict, as reflected in Decision No. 1039/Pdt.G/2023/PA.Lpk Jo No. 89/Pdt.G/2023/PTA.Mdn Jo No. 103K/Ag/2024. Using a normative juridical method with statutory and case approaches, the research focuses on examining the conformity between the Compilation of Islamic Law (KHI) and Law No. 35 of 2014 on Child Protection in relation to judicial reasoning in hadhanah (child custody) cases. The findings reveal that the Child Protection Law emphasizes legal safeguards for children, while the KHI provides detailed provisions on parental rights and responsibilities in child care. At the first level, the court granted custody to the father based on the mother’s busy work schedule, referring to Supreme Court Jurisprudence No. 110K/AG/2007. However, the appellate court ruled that such reasoning contradicted Article 105(a) of the KHI, which clearly stipulates that custody of children who are not yet mumayyiz belongs to the mother. The Supreme Court subsequently rejected the cassation appeal, affirming that the appellate decision was consistent with the law. This study underscores the importance of upholding the principle of the best interest of the child as the primary consideration in all custody determinations.